2003
DOI: 10.1002/ccd.10700
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and alternative techniques for device closure of the large secundum atrial septal defect

Abstract: Outcomes of device closure of large and small secundum atrial septal defects (ASDs) as related to rim anatomy with the Amplatzer atrial septal occluder were compared. Rim adequacy (> or = 5mm) of the anterior, inferior, posterior, and superior rims was determined using transesophageal echocardiography. Balloon-stretched defect size defined patients into two groups: group 1, < or = 25 mm (n = 138); group 2, > 25 mm (n = 34). Rim deficiency (n = 62) was more frequent in group 2 compared to group 1 (50% vs. 33%; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 23 publications
2
81
0
2
Order By: Relevance
“…42 Furthermore, the magnitude of right atrial remodeling is inversely related to patient age at the time of closure, as demonstrated in another study that reported persistent right atrial dilation in up to 64% of patients who underwent late ASD closure, which in turn was associated with elevation of brain natriuretic peptide levels and right ventricular diastolic dysfunction. 56 All these data clearly argue for early and timely closure of ASDs at the time of diagnosis.…”
Section: Cardiac Remodelingmentioning
confidence: 92%
See 1 more Smart Citation
“…42 Furthermore, the magnitude of right atrial remodeling is inversely related to patient age at the time of closure, as demonstrated in another study that reported persistent right atrial dilation in up to 64% of patients who underwent late ASD closure, which in turn was associated with elevation of brain natriuretic peptide levels and right ventricular diastolic dysfunction. 56 All these data clearly argue for early and timely closure of ASDs at the time of diagnosis.…”
Section: Cardiac Remodelingmentioning
confidence: 92%
“…Only early data are available on this point, 42 however, and patients who undergo ASD closure late, whether surgical or catheter, have been subjected to the same chronic hemodynamic burden and thus have a similar arrhythmic potential.…”
Section: Arrhythmiamentioning
confidence: 99%
“…A large defect, especially associated with deficient rims (measuring less than 5 mm from the defect to the atrial wall), may decrease the success rate of the procedure. Some authors have reported successful complete closure rates in adult patients with a defect larger than 20 mm but there is limited evidence in patients with very large defects [4,6,7]. To the best of our knowledge, this is the first report of complete percutaneous closure with the Occlutech Figulla ® in a very large ASD.…”
Section: Discussionmentioning
confidence: 89%
“…However, the indications for transcatheter approaches are limited to small secundum ASDs [2,5]. The presence of a large ASD or an insufficient rim (<5 mm) to anchor the closure device decreases the success rate of the procedure and leads to severe complications [5]. The limited long-term followup of transcatheter closure and the lack of randomized studies comparing transcatheter and surgical closures make it imprudent to conclude that transcatheter closures are comparable or even preferable to the surgical approach, regardless of patient selection.…”
mentioning
confidence: 99%
“…The success rate of transcatheter closure is reported to be 95% to 98% [2][3][4]. However, the indications for transcatheter approaches are limited to small secundum ASDs [2,5]. The presence of a large ASD or an insufficient rim (<5 mm) to anchor the closure device decreases the success rate of the procedure and leads to severe complications [5].…”
mentioning
confidence: 99%